International journal of mechanical and materials engineering ([Singapore] : Springer Singapore)
International Journal of Material and Mechanical Engineering (IJMME) is an internationally refereed journal dedicated to publishing the latest advancements in material and mechanical engineering research. The goal of this journal is to record the latest findings and promote further research in these areas. Scholars from all relevant academic fields are invited to submit high-quality manuscripts that describe the latest, state-of-the-art research results or innovations.
Description based on: Volume 9, issue 1 (December 2014) ; title from caption (Springer, viewed July 11, 2016).
Latest issue consulted: Volume 12, issue 1 (December 2017) (viewed November 02, 2017).
Keywords: Mechanical engineering -- Periodicals; Materials -- Mechanical properties -- Periodicals; Materials -- Mechanical properties; Mechanical engineering; Mechanical Engineering - General; Electronic journals